L’art face au livre - Pascal Krajewski (Appareil)
The article analyzes the various ways of articulating together the four concepts of the debate: the book, the medium, the text, and the work of art. Schematically, this encounter through the book object outlines three distinct regions : where the book plays a documentary role in relation to an external work of art, where it plays the role of an element integrated into a comprehensive visual artwork, and where it functions itself as a work of art in its own right.The aesthetic effects of books on the art objects they refer to are examined to show how they oscillate between aesthetic neutrality and media reinvention, including the addition of a sensual or symbolic charge.Finally, the article focuses on what it calls “bookish arts,” encompassing pop-ups and manuscripts as well as artist’s books and illustrated books, to precisely describe each piece of this patchwork where the book truly becomes the work of art.